Stop avoiding the inevitable: The effects of anthropomorphism in science writing for non-experts. (July 2021) - McGellin, Rockwell Tomson Lyon; Grand, Ann; Sullivan, Miriam
While anthropomorphism – the attribution of human characteristics to non-human things or events – is a fundamental part of human psychology and language, some scientists regard it as a source of misconceptions. This creates tension for those writing about science. Taking an experimental approach to diagnosing misconceptions, we compared the effects of anthropomorphic and non-anthropomorphic writing on 174 adult readers' knowledge, understanding, confidence in and connection with the material. Reading any text at all improves readers' knowledge and ability to answer questions. There was no difference in understanding, enjoyment or frequency of anthropomorphic thinking between anthropomorphic and non-anthropomorphic texts. Those who read anthropomorphic text tended to use more vivid examples and fewer generalisations. This suggests that anthropomorphism acts as an evocative, albeit potentially distracting, technique but does not cause significant misconceptions. Writers should feel free to use anthropomorphic techniques if they are appropriate for their topic and their audience.